Ion channel modulation by NS 1619, the putative BKCa channel opener, in vascular smooth muscle - Edwards, G; Niederste-Hollenberg, A; Schneider, J; Noack, T; Weston, A H (British journal of pharmacology, 1994)
1. The effects of NS 1619, the putative BKCa channel opener, were investigated on rat intact portal veins and on single smooth muscle cells enzymatically separated from the same tissue. 2. Under whole-cell patch clamp conditions with K-rich pipettes, exposure of single cells held at -10 mV to NS 1619 (10-33 microM) induced a noisy, outward current which reached a maximum (33 microM NS 1619; mean 35.8 +/- 17 pA, n = 8) within about 6 min. 3. On stepping to test potentials (range -50 to +50 mV) from a holding potential of -10 mV, the NS 1619-induced noisy current exhibited time-dependent activation and marked outward rectification. 4. The stimulation of outward currents by NS 1619 at -10 mV was independent of the presence of Ca2+ in the bath or pipette solutions but was antagonized by either charybdotoxin (250 nM) or penitrem A (100 nM) in the bath solution. 5. Stationary fluctuation analysis of the noisy current induced by NS 1619 at -10 mV yielded a value of 70 +/- 8 pS (n = 4) (under the quasi-physiological conditions of the experiment) for the unitary conductance of the channel involved. 6. At -10 mV, NS 1619 (10-33 microM) rapidly inhibited spontaneous transient outward currents. 7. With a holding potential of -90 mV, NS 1619 (10-33 microM) produced a reduction of outward currents evoked by depolarizing steps to +50 mV, an effect associated with marked inhibition of the delayed rectifier current, IK(V). 8. NS 1619 (3-100 microM) produced a concentration-dependent inhibition of spontaneous activity in rat portal vein characterized by a reduction in the amplitude and duration of the tension waves. This inhibition was slightly potentiated in the presence of either charybdotoxin (250 nM) or penitrem A (1 microM). NS 1619 also totally inhibited contractions of rat aorta induced by KCl (both 20 mM and 80 mM). 9. Under whole-cell recording conditions and using Cs-rich pipettes, Ca-currents evoked in portal vein cells by stepping from a holding potential of - 90 mV to test potentials in the range - 30 to + 50 mV were totally inhibited in the presence of 33 JAM NS 1619.10. NS 1619 (33 JAM) inhibited the induction of IK(ATP) by levcromakalim (10 JAM).11. It is concluded that NS 1619 activates the large conductance, Ca2+-sensitive channel, BKca and over the same concentration range it inhibits both KV and L-type Ca-channels. The observed NS 1619-induced mechanical inhibition in rat portal vein and aorta seems most likely to be due to the observed inhibition of Ca-currents.